EFEKTIFITAS DAUN SIRIH MERAH UNTUK MENURUNKAN KADAR GULA DARAH PADA PENDERITA DIABETES MELLITUS - Suryono, Suryono (Jurnal AKP, 2012)
Diabetes Mellitus is a disease in which blood glucose levels was high because the body can not use insulin adequately. High blood sugar levels will cause complications such as coronary artery disease, stroke, gangrene, and diabetic retino erectile dysfunction. The purpose of this research was to identify the effectiveness of piper crocatum leaves to lower blood sugar levels in diabetes mellitus patient.Design used in this study is pre experimental design with one group pre-post test design. Population of all patients of Diabetess Melitus in Puskesmas kepung amount to 25 people, 10 respondents sample, sampling technique is purposive sampling. Then processed with editing, coding, tabulating. Data is presented in the form of pie charts. Data analysis was done by identifying the level of blood glucose before and after treatment. Analyze inferentially that processed with  SPSS software 14 to determine the average and standard deviation.The research results showed that respondents that amount to 10 people happened the decrease in blood sugar levels from 209.30 mg / dl to 186.30 mg / dl in other words, blood glucose decreased by  12,6 %.From the research results can be concluded that there is a decrease in blood sugar levels after given therapy  of piper crocatum leaves during 7 days, meant piper crocatum  leaves was effective to lower blood sugar levels in diabetes mellitus.